Fecal and oral microbiome analysis of snakes from China reveals a novel natural emerging disease reservoir - Hu, Xiaoliang; Yang, Lu; Zhang, Yue; Yang, Manman; Li, Jiayi; Fan, Yuping; Guo, Peng; Tian, Zhige (Frontiers in Microbiology, 2024)
The gastrointestinal tract and oral cavity of animal species harbor complex microbial communities, the composition of which is indicative of the behavior, co-evolution, diet, and immune system of the host. This study investigated the microbial composition in snakes from varying altitudinal ranges by assessing the fecal and oral bacterial communities in Protobothrops mucrosquamatus, Elaphe dione, and Gloydius angusticeps from Sichuan Province, China, using metagenomic sequencing. Results revealed that Bacteroidetes, Proteobacteria, Firmicutes, and Fusobacteria were the core microbial phyla in fecal samples across all three species, while Proteobacteria, Bacteroidetes, Actinobacteria, and Firmicutes were the core microbial phyla in oral samples across all three species. Notably, the dominance of Armatimonadetes was documented for the first time in the feces of all three species. Comparative analysis of the microbiomes of the three species indicated distinct microbiological profiles between snakes living at low-and high-altitude regions. Furthermore, 12 to 17 and 22 to 31 bacterial pathogens were detected in the oral and fecal samples, respectively, suggesting that snakes may serve as a novel reservoir for emerging diseases.Overall, this study provides a comparative analysis of the fecal and oral microbiomes in three snake species. Future investigations are anticipated to further elucidate the influence of age, genetics, behavior, diet, environment, ecology, and evolution on the gut and oral microbial communities of snakes.